The long-term impact of lecturer talk on student learning: Japanese students’ reflections - Bao, Dat (Neofilolog, 2024)
This pragmatic case study explores Japanese students’ perceptions of lecturer talk in an Australian higher-education setting. The main findings cover two sections. The first section discusses positive talk focusing on pedagogical strategies that enhance student engagement. Teachers can create a stimulating learning environment that fosters active participation and meaningful connections with students through personal anecdotes, real-world applications, and interactive discussions. The second section examines negative talk with poor impact on student learning experiences. Issues such as lack of clarity, low interaction, and undesirable teaching approaches hinder students’ comprehension and engagement, highlighting the importance of effective communication strategies in facilitating learning. The article concludes with practical recommendations provided by students to improve teacher communication and enhance the overall learning experience, emphasising the significance of student-centred, engaging, and inclusive teaching practices in promoting compelling lecturer talk.